Analysis Of The Geothermal Potential Based Fault Zone In Burni Telong Bener Meriah, Aceh, Indonesia - Gartika Setiya Nugraha; Marwan Marwan; Oky Ikhramullah; Susanti Alawiyah; Sutopo Sutopo (UNEJ e-Proceeding, 2016)
Mount of Burni Telong located in Bener Meriah, Aceh, Indonesia is one of the mountains that have the potential for development of renewable energy from geothermal sources, but is still untapped. The evidence suggests that, to date Aceh still depends on power supplies from North Sumatra. This dependence often affects alternate electricity blackouts all over the province so that the necessary rationale for their source of power generation in Aceh. The purpose of this study was to analyze the potential development of Burni Telong as geothermal energy power plant in Aceh, Indonesia.This study was a survey with the approach in the field of geophysics. Analysis of potential geothermal done using the gravity method to investigate the distribution of mass in the subsurface. The study found that there are two tracks, namely: A-A' and B-B track'. A-A' tracks has four layers, composed of: Riolitic Tuff (1.77g/cm3), basaltic Tuff (2:12 gr/cm3), Diorites (2.78 gr/cm3),and basalt (3:00 gr/cm3). B-B' tracks has three layers, namely: Basaltic Tuff (2.12 gr/cm3); Diorites (2,78 gr/cm3), and basalt (3.00 gr/cm3). In both of these trajectories found two faults, namely: normal and Horst. It can be concluded that the difference in density contrast and hot springs that are parallel to the fault indicates a fault in Burni-Telong, so Burni Telong has the potential Geothermal and very likely to be developed as a source of electricity generation from geothermal energy in Aceh, Indonesia.